Codes of groupoids with one-sided quasigroup conditions - Ga̷luszka, J. (Algebra and Discrete Mathematics, 2009)
We propose a method of description of quasigroup conditions defining one-sided quasigroup classes and onesided quasigroup varieties by number codes. This method can be used for all one-sided quasigroups. In order to construct the code words we use the technique of Steinitz numbers.